RETRACTED: Psychometric Assessment of the Persian Translation of the Interpersonal Mindfulness Scale With Undergraduate Students - Abdollahi, Abbas; Vadivel, Balachandran; Huy, Dinh Tran Ngoc; Opulencia, Maria Jade Catalan; Van Tuan, Pham; Abbood, Abbas Abd Ali; Nasirova, Zarina; Chupradit, Supat; Allen, Kelly A.; Bykanova, Olga (Frontiers in Psychiatry, 2022)
Interpersonal mindfulness is a construct that significantly contributes to social interaction. To date, no validated measure assessing interpersonal mindfulness has been developed in (Name of country). Therefore, the aim of this study was to translate and validate the Interpersonal Mindfulness Scale (IMS; Pratscher et al., 2019) among (Nationality) undergraduate students. Participants in the study (370 undergraduate students; 220 females) from the (Name of university) University completed the translated IMS, the Five Facet Mindfulness Questionnaire, and the Inventory of Interpersonal Problems Scale. The translated measure demonstrated acceptable face validity. All items had acceptable content validity and were deemed essential to the scale. The results of a Confirmatory Factor Analysis (CFA) confirmed a scale with four subscales (presence, awareness of self and others, nonjudgmental acceptance, and non-reactivity), with acceptable internal consistency. The findings support the psychometric properties of the (language) translated Interpersonal Mindfulness Scale, which could be used to measure interpersonal mindfulness among undergraduate students in (Name of country).